A Medical Home for Children with Special Health Care Needs in Rural Locations - Amy J McClune (Rural Nurse Organization; Binghamton University, 2012)
Children with special health care needs (CSHCN) present a complex challenge to the medical system. The concept of a medical home has been proposed to ensure consistency and continuity of care for CSHCN. Although it seems to be an easy solution in theory, implementation is complicated especially for the child residing in a rural area. This paper will explore the possibilities to ensure that rural CSHCN have access to a medical home. The characteristics of a medical home include continuity, accessibility, coordination and compassion. A comprehensive focus on the family with attention to cultural needs is critical. Geography, transportation, and financial barriers are present in rural families of CSHCN. In a five-year longitudinal study, Adams and colleagues (2006) found unmet dental, visual, and auditory health needs in school-age children in the rural south. Primary care in general was also identified as an unmet need. Nora Pender‟s model of health promotion (2006) provides a strong framework for assessing and implementing the medical home concept for CSHCN in rural areas. Individual characteristics include the psychological and socio-cultural components of a rural lifestyle. Accessibility issues may prevent optimal health promotion and illness prevention in a CSHCN in a rural area. Using data from the National Survey of CSHCN, Skinner and Slifkin (2007) examined barriers faced by rural families of CSHCN that fit with the behavior specific cognitions and affect described by Pender. Using Pender‟s model of health promotion (2006) provides a successful template for providing a medical home for CSHCN living in rural areas. Involving health care providers, home health agencies and community resources under the leadership of an advanced practice nurse could provide the chemistry needed for success.